The jubilee year of the Reformed Apostolic Faith Mission of South Africa - S Moripe (Acta Theologica)
Africans celebrate life just like Jewish people. They celebrate their religion, they dance it, they sing it and they act it. They have innumerable rituals and ceremonies. Some rituals are personal others are related to agriculture, health, homestead, profession and festivals. Through festivals, the life of a community is renewed. Hence the Reformed Apostolic Faith Mission of South Africa celebrated its Jubilee in 1997. This church was founded in 1947, in Krugersdorp (Gauteng Province), after breaking away from the Apostolic Faith Mission of South Africa, due to religious, social and political reasons.